Prognostic value of cachexia index in patients with colorectal cancer: A retrospective study - Wan, Qianyi; Yuan, Qian; Zhao, Rui; Shen, Xiaoding; Chen, Yi; Li, Tao; Song, Yinghan (Frontiers in Oncology, 2022)
Background: To investigate the prognostic value of a novel cachexia indicator, the cachexia index (CXI), in patients with colorectal cancer. Methods: The CXI was calculated as skeletal muscle index (SMI) × serum albumin / neutrophil-lymphocyte ratio. The cut-off value of CXI was determined by the receiver operating characteristic (ROC) curves and Youden's index. The major outcomes were major complications, overall survival (OS), and recurrence-free survival (RFS). Results: A total of 379 patients (234 men and 145 women) were included. The ROC curves indicated that CXI had a significantly diagnostic capacity for the detection of major complications (AUC: 0.671; 95%CI: 0.566 to 0.775; P= 0.005). Based on Youden's index, there were 231 and 148 patients in the low and high CXI groups, respectively. Patients in the low CXI group had significantly older age, lower BMI, and a higher percentage of TNM stage II and III. Besides, Patients in low CXI group were associated with a significantly higher rate of major complications, blood transfusion, and longer length of stay. Logistic regression analysis indicated that low CXI and coronary heart disease were independent risk factors for the major complications. Kaplan Meier survival curves indicated that patients with high CXI had a significantly more favorable OS than those with low CXI, while no significant difference was found in RFS between the two groups. The univariate and multivariate Cox regression analysis indicated that older age, low CXI, and coronary heart disease were associated with a decreased overall survival. Conclusion: CXI could be a useful prognostic indicator in patients with colorectal cancer, and a lower CXI is associated with an increased risk of major complications and decreased overall survival.